Theoretical Review of Phonics Instruction among EFL Beginner-level Readers in China - Minjie, Chen; Guojie, Yin; Hock Seng, Goh; Ruey Shing, Soo (Human Resource Management Academic Research Society, 2022)
This article aims to conduct a theoretical review of phonics and its instruction among EFL beginners in China to provide an overall understanding of the basic concepts of phonics and phonics instruction, as well as the relevant theories. Based on previous literature, the findings indicated that phonics refers to the letter-sound relationship and that phonics instruction is the optimal teaching activity through which to implement phonics. Three major phonics instruction approaches can be identified, of which the synthetic phonics instruction approach might be the most appropriate for EFL beginners. In addition, to enhance the effects obtained from phonics instruction, beginners should be prepared with knowledge of the alphabet and phonemic awareness. Finally, certain relevant theories, such as behaviourism and constructivism, may provide the theoretical foundation for phonics and its instruction in EFL settings in China.